Comprehensive investigation of cucumber heat shock proteins under abiotic stress conditions: A multi-omics survey - Unel, Necdet Mehmet; Baloglu, Mehmet Cengiz; Altunoglu, Yasemin Çelik (Elsevier BV, 2023)
Heat-shock proteins (Hsps) are a family of proteins essential in preserving the vitality and functionality of proteins under stress conditions. Cucumber (Cucumis sativus) is a widely grown plant with high nutritional value and is used as a model organism in many studies. This study employed a genomics, transcriptomics, and metabolomics approach to investigate cucumbers' Hsps against abiotic stress conditions. Bioinformatics methods were used to identify six Hsp families in the cucumber genome and to characterize family members. Transcriptomics data from the Sequence Read Archive (SRA) database was also conducted to select CsHsp genes for further study. Real-time PCR was used to evaluate gene expression levels under different stress conditions, revealing that CssHsp-08 was a vital gene for resistance to stress conditions; including drought, salinity, cold, heat stresses, and ABA application. Gas Chromatography-Mass Spectrometry (GC-MS) analysis of plant extracts revealed that amino acids accumulate in leaves under high temperatures and roots under drought, while sucrose accumulates in both tissues under applied most stress factors. The study provides valuable insights into the structure, organization, evolution, and expression profiles of the Hsp family and contributes to a better understanding of plant stress mechanisms. These findings have important implications for developing crops that can withstand environmental stress conditions better.
Keywords: Gene Expression Profiling; Multiomics; Stress, Physiological; Gene Expression Regulation, Plant; Cucumis sativus; Heat-Shock Proteins; Phylogeny; Plant Proteins; 2. Zero hunger; 15. Life on land; 6. Clean water; 3. Good health